2013
DOI: 10.3917/spub.253.0305
|View full text |Cite
|
Sign up to set email alerts
|

L'influence des technologies de l'information et des communications sur le maintien en poste des infirmières

Abstract: The main findings indicate significant heterogeneity, both in terms of the nursing shortage and in terms of the integration of ICT in nursing practice. While focusing on a comparative approach, future research should further explore the impact of ICT on nursing practice and, indirectly, on nurse retention, which requires a contextual approach to ICT applications and workplaces and an analysis of staff characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The results revealed that, in 9 out of the 13 studies, ICT use demonstrated a positive, though often indirect, influence on recruitment and retention. The influence of ICTs on retention of nurses was also examined in a qualitative study [63]. The results highlighted various impact of ICTs on nurse retention (ie, little or no impact, unclear impact, or indirect positive impact).…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that, in 9 out of the 13 studies, ICT use demonstrated a positive, though often indirect, influence on recruitment and retention. The influence of ICTs on retention of nurses was also examined in a qualitative study [63]. The results highlighted various impact of ICTs on nurse retention (ie, little or no impact, unclear impact, or indirect positive impact).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, unlike previous research, 23 the theme of professional autonomy was subsumed within professional development.…”
Section: Discussionmentioning
confidence: 67%
“…With respect to retention, we observed different perceptions of participants, similar to those observed in the first phase of our research. Indeed, in a study conducted among nursing managers from 16 healthcare organizations in the Province of Quebec, 23 we found limited support for a direct influence of ICT on nurse recruitment and retention. However, unlike previous research, we observed a greater enthusiasm among participants who emphasized positive effects of the service on retention.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Information and communication technologies (ICTs) embody all digital technologies that support the electronic capture, storage, processing, and exchange of information in order to promote health, prevent illness, treat disease, manage chronic illness, and so on [ 1 , 2 ]. In the health sector, ICTs refer to a set of projects or services that allow for remote care (telehealth), interdisciplinary clinical support, as well as knowledge transfer [ 3 ]. The use of ICTs has the potential to promote patient-centered healthcare at a lower cost, improve quality of care and information sharing, educate health professionals and patients, encourage a new form of relationship between patients and their health providers, reduce travel time, etc.…”
Section: Introductionmentioning
confidence: 99%